Henrietta Kent and the Feminised North - Hansson, Heidi (Nordlit, 2007)
Some time around 1876, S. H. Kent, Susanna Sarah Henrietta Kent or Henrietta Kent as she probably called herself, travelled through the northern parts of Norway and Sweden with her elderly mother. Her impressions from the northern trip were published in two volumes entitled Within the Arctic Circle: Experiences of Travel through Norway, to the North Cape, Sweden and Lapland, advertised in The Times 6 February 1877. There was a great deal of public interest in the Arctic at the time due to the scientific and cultural activity leading up to the first International Polar Year 1882-83. Kent, however, does not foreground the adventure and excitement associated with the Polar expeditions in her narrative. Instead, she concentrates on the kind people and pleasant aspects of northern Scandinavia, asserting that the difficulties of northern travel have been exaggerated and that nothing should "deter even lady travellers" from going North. At least as she presents the exercise in her preface, travelling in Norway and Sweden requires no particular strength or stamina. The dangers of the wild as well as the romance of the Arctic are absent from her book, making northern Scandinavia seem quite woman-friendly. Kent's travelogue demonstrates in many ways the interaction between the construction of a gendered narrative self and the gendering of place.